High-entropy spinel oxides: Structural and magnetic characterization through neutron diffraction (2024)
High entropy oxides (HEOs) represent a paradigm changing field of research that has awakened a lot of attention from physicists, material scientists and chemists. They are a new class of ceramic material that includes 5 or more transition metals (TMs) in its crystal lattice. Besides from the wide range of applications in biomedicine, energy and data storage due to their electrical, catalytic and magnetic properties; spinel HEOs are a way to question what properties emerge from extreme configurational disorder in contrast to common iron- or chromium-based spinels. This project aims to unveil both structural and magnetic properties of the spinel HEOs (Cr0.2Mn0.2Fe0.2Co0.2Ni0.2)3O4, (Co0.33Ni0.33Cu0.33 (Mn0.5Fe0.5)2O4, and (Co0.33Ni0.33Cu0.33)(Cr0.33Mn0.33Fe0.33)2O4 in order to investigate if they differ from a simple average of the common TM-based spinel. To do this, single-phase spinel HEOs were synthe- sized through a sol-gel method at the Center for High Entropy Alloy Catalysis (CHEAC) at the University of Copenhagen (UCPH), Denmark. Powder X-ray diffraction (PXRD) was performed on all three HEOs at UCPH, Denmark; to check the quality of the samples. Moreover, isothermal curves of magnetization as a function of applied magnetic field were measured at T = 2 and 300 K, as well as field cooled (FC) M-T susceptibility measurements for T < 300 K. To find the paramagnetic transition temperature Tc on each HEO, FC magnetic susceptibility was measured up to 550 K at the University of California San Diego (UCSD), United States. Ultimately, to fully characterize the magnetic structure of the HEOs, temperature dependent powder neutron diffraction (PND) was performed using the High-Resolution Powder Diffractometer for Thermal Neutrons (HRPT) at Paul Scherrer Institute (PSI), Switzerland. From the above experimental techniques, single phase HEOs with cubic spinel structure (space group Fd¯3m) were identified with no detectable impuri- ties. Hysteresis loops at low temperatures and characteristic soft magnetic behaviour at room temperature was observed. Ferrimagnetic ordering in every HEO was confirmed through low temperature magnetometry and PND with their corresponding transition temperature. Finally, there were several effects of the high-entropy nature on the HEOs behaviour such as spin glass states at room temperature and ferrimagnetic ordering. The former property seems to be a direct consequence of both high configurational entropy and the symmetries of the spinel structure.